Educación virtual y su efecto en el rendimiento académico de los estudiantes de Comunicación Social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2022 - Castro Ochoa, Drexer Eduardo (2022)
The following research refers to how virtual education has generated positive and negative effects on the academic performance of social communication students, it is for this reason that it was investigated how the new study modality is taking place and a comparison was made with the level of learning acquired in face-to-face classes as opposed to virtual classes. This research seeks to be a means of support to solve the different problems, benefiting students of social communication, analyzing how virtual education influences, it was possible to identify the differences in advantages and disadvantages of it and the effect of this change is studied. The sample is taken from 142 students, of the 224 who were the total number of students of the social communication career at the Technical University of Babahoyo, Quevedo extension. In conclusion, virtual education was influential both in the qualifications and in the academic performance of the students, as a recommendation I hope that the next academic period will be carried out in person so that the students can carry out the practical classes that are very necessary in professional training. and when the occasion warrants, the virtual platform is used.